Ideological symmetry in out-group bias: a neuroimaging study in the context of vaccine hesitancy - Kluge, Annika; Levy, Jonathan (Frontiers in Social Psychology, 2024)
One of the most contentious debates in political psychology relates to the existence of ideological (a)symmetry in out-group bias. Recent neuroimaging and psychological studies circumvented previous criticisms regarding the inclusion of ideologically biased out-groups by directly targeting the ideological out-groups themselves (rightists for leftists and leftists for rightists). Their findings confirmed the asymmetry claim, with particularly robust and informative results at the neural level. Nevertheless, the recent pandemic provided a new opportunity for the investigation of ideological (a)symmetry in out-group bias by introducing an ideologically neutral yet highly discriminated and stigmatized group—vaccine-hesitant individuals. In this preregistered study, 50 Finnish adults were scanned using magnetoencephalography to delineate function-specific neural mechanisms of bias against vaccine hesitancy. The results show a clear neural bias against vaccine hesitancy regardless of political inclination. The findings reported here contribute to the present debate by selecting a unique ideologically neutral target and revealing that ideological (a)symmetries in out-group bias are highly context-dependent.